Challenges in Operating University Moodle E-Learning: A Case Study from Lecturers’ Perceptions - Juliana, I Putu; Utami, I.G.A Lokita Purnamika; Utami, Ida Ayu Made Istri (Universitas Negeri Malang, 2021)
Abstrak: Penelitian bertujuan untuk menginvestigasi persepsi tentang kesulitan dosen Pendidikan Bahasa Inggris yang menggunakan E-learning Moodle Undiksha dalam mata kuliah pedagogi, literature, reading dan writing. Penelitian ini menggunakan metode mix dan lebih kepada pendekatan kualitatif. Peneliti menggunakan kuisioner dan panduan interview saat pengumpulan data. Dosen Pendidikan Bahasa Inggris merupakan partisipan dalam penelitian ini. Hasil penelitian menunjukan ada enam masalah yang ditemui oleh dosen saat menggunakan E-learning Moodle Undiksha yang di kategorikan menjadi internal dan external. Kesulitan internal yang ditemui berupa tidak adanya fitur auto-refresh, konferensi video, pesan suara dan mengedit secara berkesinambungan. Sedangkan untuk halangan external diantaranya sikap buruk plagiarism dan partisipasi pasif dari mahasiswaAbstract: This research aimed to investigate the perceptions about challenges that are encountered by English Language Education lecturers using the Undiksha Moodle e-learning in pedagogy, literature, reading, and writing course. This study used an embedded mixed-method case study with qualitative dominant. Questionnaire and semi-structured interviews were used by the researcher in collecting the data. The participants were the lecturers of English Language Education. The findings manifested that there were six challenges that were encountered by the lecturers during operating the Undiksha Moodle e-learning that could be categorized into internal and external. The internal challenges such as the absence of several features like auto-refresh, video conference, voice message recording, and editing synchronously. While the external challenges were the bad attitude of the plagiarism act and students’ passive participation